Prevalence of anemia and associated factors in older adults: evidence from the SABE Study - Ligiana Pires Corona; Yeda Aparecida de Oliveira Duarte; Maria Lucia Lebrão (Universidade de São Paulo, 2014)
OBJECTIVE To assess the prevalence of anemia and associated factors in older adults. METHODS The prevalence and factors associated with anemia in older adults were studied on the basis of the results of the Saúde, Bem-Estar e Envelhecimento (SABE - Health, Welfare and Aging) study. A group of 1,256 individuals were interviewed during the third wave of the SABE study performed in Sao Paulo, SP, in 2010. The study included 60.4% females; the mean age of the participants was 70.4 years, and their average education was 5.3 years. The dependent variable was the presence of anemia (hemoglobin levels: 12 g/dL in women and 13 g/dL in men). Descriptive analysis and hierarchical logistic regression were performed. The independent variables were as follows: a) demographics: gender, age, and education and b) clinical characteristics: self-reported chronic diseases, presence of cognitive decline and depression symptoms, and body mass index. RESULTS The prevalence of anemia was 7.7% and was found to be higher in oldest adults. There was no difference between genders, although the hemoglobin distribution curve in women showed a displacement toward lower values in comparison with the distribution curve in men. Advanced age (OR = 1.07; 95%CI 0.57;1.64; p < 0.001), presence of diabetes (OR = 2.30; 95%CI 1.33;4.00; p = 0.003), cancer (OR = 2.72; 95%CI 1.2;6.11; p = 0.016), and presence of depression symptoms (OR = 1.75; 95%CI 1.06;2.88; p = 0.028) remained significant even after multiple analyses. CONCLUSIONS The prevalence of anemia in older adults was 7.7% and was mainly associated with advanced age and presence of chronic diseases. Thus, anemia can be an important marker in the investigation of health in older adults because it can be easily diagnosed and markedly affects the quality of life of older adults.